Imaging and Urodynamics of the Lower Urinary Tract - Patel, Uday.; SpringerLink (Online service) (London : Springer London, 2010)
Imaging of the Lower Urinary Tract is a practical, user-friendly aid to planning a thorough radiological and dynamic investigation of the lower urinary tract. It provides a holistic approach, marrying the diagnosis of both anatomical and functional abnormalities. Both comprehensive and concise, this book covers the range of lower urinary tract disorders that are commonly encountered in adult urological practice whilst presenting the information clearly. Key point summaries further aid quick reference in the clinical setting. Dr Uday Patel, MBChB MRCP FRCR is Consultant Uro-Radiologist at St Georges Hospital and The Princess Grace Hospital, London, UK. He is an internationally recognized expert in urological imaging, as both a practitioner and teacher.
The Bladder -- The Normal Bladder -- Imaging Modalities Used for Assessment of the Bladder -- Congenital Anomalies of the Bladder -- Intraluminal Abnormalities of the Bladder -- Abnormalities of the Bladder Wall or Mural Abnormalities -- Staging of Bladder Cancer -- Abnormal Bladder Contour or Size -- Functional Abnormalities of the Bladder -- The Urethra -- The Normal Urethra -- Congenital Anomalies of the Urethra -- Intraluminal Abnormalities and Filling Defects of the Urethra -- Intrinsic Abnormalities of the Urethral Wall -- Lower Urinary Tract Trauma -- Neoplasms of the Urethra.
Keywords: Medicine; Radiology, Medical; Urology; Medicine & Public Health; Urology/Andrology.; Imaging / Radiology